KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN DASAN GUNDUL, DESA MENEMENG, KECAMATAN PRINGGARATA, KABUPATEN LOMBOK TENGAH - Herliana; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Menemeng is one of the villages in Pringgarata District, Central Lombok Regency. The research was conducted using the observation method. Based on the research, it is known that the yard plants in Dasan Gundul Hamlet, Menemeng Village, Pringgarata District, Central Lombok Regency, have H’= 2.47, which means moderate diversity, moderate distribution, and moderate community stability.